Akinetes From Late Paleoproterozoic Salkhan Limestone (>1600 Ma) of India: A Proxy for Understanding Life in Extreme Conditions - Sharma, Mukund; Shukla, Bandana (Frontiers in Microbiology, 2019)
Isolated elongate spore-like cells present in the >1600 Ma old Salkhan Limestone of the Semri Group, Vindhayan Supergroup, India are considered akinetes of the heterocystous cyanobacteria. Small to large size, and young (single walled) to mature (double walled) akinetes namely, Archaeoellipsoides bactroformis, A. conjuctivus, A. dolichos, A. elongatus, A. grandis, A. major and A. minor found in the stromatolitic and bedded cherts have been reported in the present paper. Their role in understanding extreme environmental conditions is a subject matter of this paper. Additionally, the occurrences of doubly-terminated quartz crystals and fan-fabrics in the Salkhan Limestone indicate adverse conditions for the survival of life forms. The depositional environment of the Salkhan Limestone, Vindhyan Supergroup is suggested to be shallow marine intertidal with pulses of the intermittent hypersaline regime during which akinetes, closely resembling those of extant Nostocaceans, were formed by the cyanobacteria for survival in the extreme conditions.